Modulação de efeitos das decisões de inconstitucionalidade do Supremo Tribunal Federal em matéria tributária - Halabe, Maria Tereza Ramos Vale (2022)
On the present research the study was centered in the legal institute of effects modulation in face of unconstitutionality decisions handed down by the Federal Supreme Court (STF) in tax matters, both in concrete and abstract control of constitutionality, analyzing, in a qualitative way, the jurisprudence of the Court of the last five years, in particular the decisions in which there was a discussion about the modulation of effects. Since, among other requirements imposed by Laws nº 9.868/1999 and nº 9.882/1999, the modulation of effects is applied based on the undetermined concepts of “legal certainty” and “exceptional social interest”, it is questioned whether the decisions of the STF maintain interpretative coherence and whether such coherence is in accordance with the Constitution. It must be emphasized that vague concepts can give ample freedom to the interpreter unless some parameters are obeyed. Therefore, it is expected to bring contributions to the discussion about the modulation of effects institution applicability in tax matters, investigating the Court's argumentative field to support the modulation. This discussion is of great relevance, in view that the impact of the STF decisions on the other Judiciary Branch agencies and on society in general, with particular emphasis in the present work, on the taxpayer's private sphere, since the field of research of the present dissertation is dedicated to decisions in tax matters. The method of approach adopted was the hypothetical-deductive, in which, based on the jurisprudence of the STF, evidence able to refute the raised hypotheses, that is, there is a decision parameter in relation to the scope and meaning of the material requirements for the application of effects modulation and this parameter is constitutional. As a result, there was a need for the Court to establish, for the requirements of exceptional social interest and legal certainty, more aligned edges with fundamental rights. Because this lack of delimitation, in the first case, implied a merger with the interest of the State-administrator and, in the second case, a merger with the idea of fiscal security. As it allows the application of the subjective aspect of legal certainty in favor of the State alongside the exceptional public interest, modulation becomes an institute in defense of budgetary matters.